Communication Strategy of Legal Aid Center for The Press in Advocating The Issue of Violation of Rights of Media Workers in The Covid-19 Pandemic - Abdul Rahman; Jamiyatun Jamiyatun; Rini Sudarmanti (Research Synergy Foundation, 2022)
Background - Several media companies have violated labor rights against their workers under the pretext of efficiency due to the impact of the Covid-19 pandemic. Aggrieved media workers complained to Legal Aid Center for The Press (LBH Pers) for legal assistance. Legal Aid Center for The Press as an Indonesia civil society organization provides legal assistance and advocacy to media workers who have been harmed by media companies under this pretext. Purpose – This study aims to determine the communication strategy used by Legal Aid Center for The Press in advocating the issue of violations of media workers rights during the Covid-19 pandemic. Design/methodology/approach – This study uses a qualitative method with a case study approach. Data collection was carried out by in-depth interviews with Director of Legal Aid Center for The Press Ade Wahyudin and Media Relations Manager Mustafa Layong, and collecting documents related to cases of media worker rights violations during the Covid-19 pandemic. Findings – The result of this research is that the Legal Aid Center for The Press has actively implemented a communication strategy through press releases, press conferences, and public discussions. The communication strategy involves the media with the aim of giving public pressure to media entrepreneurs as well as a means of education, and building solidarity among media workers. Research limitations– The scope of this research is only on the communication strategy carried out by Legal Aid Center for The Press on the issue of violations of media workers' rights related to the Covid-19 pandemic based on the number of complaints that came in throughout 2020. Originality/value – This case is unique because it occurred during the Covid-19 pandemic so it's happened for the first time and there is less discussed research on the communication strategy of Non-Governmental Organizations (NGOs) that oversee the issue of violations of media workers' rights during the Covid-19 pandemic.